2020
DOI: 10.3390/jcm9103103
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Care in Psoriatic Arthritis—A Perspective on Inflammation, Disease Activity, and Psychosocial Factors

Abstract: Psoriatic arthritis (PsA) is a seronegative spondyloarthropathy characterized by skin lesions, dactylitis, and enthesitis. Patients with PsA suffer from a variety of psychosocial difficulties and nonspecific symptoms early on in the disease course and continue to experience progressive disease due to delays in diagnosis and treatment. Symptoms initially viewed as somatization could lead to undertreatment and promote psychological distress, poor coping, and negative patient–provider relationships. Pain and fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 113 publications
(128 reference statements)
0
15
0
Order By: Relevance
“…The visualization of changes in microcirculation and vascularization by FOI may enable the detection of a very early PsA disease state in a presubclinical phase -in transition to a clinical stage (29). This is underlined by the hypothesis that non-specific musculoskeletal symptoms in patients with psoriasis may actually represent a preclinical phase of PsA (30,31). In addition, Faustini et al reported that the risk for developing PsA was as high as 60% if patients had subclinical synovitis and symptoms related to arthralgia highlighting the importance to establish an early PsA diagnosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…The visualization of changes in microcirculation and vascularization by FOI may enable the detection of a very early PsA disease state in a presubclinical phase -in transition to a clinical stage (29). This is underlined by the hypothesis that non-specific musculoskeletal symptoms in patients with psoriasis may actually represent a preclinical phase of PsA (30,31). In addition, Faustini et al reported that the risk for developing PsA was as high as 60% if patients had subclinical synovitis and symptoms related to arthralgia highlighting the importance to establish an early PsA diagnosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia, or the inability to describe one's emotions, positively correlates with somatization in patients with psoriasis, especially in women and also when the face, hands or genitals are involved 25,26 . Psoriatic arthritis (PsA) is a seronegative spondyloarthropathy characterized by skin lesions, dactylitis, and enthesitis 27 . Patients with PsA often suffer from a number of psychosocial problems and also nonspecific symptoms early on in the course of the disease 27 .…”
Section: Somatization and Psoriasismentioning
confidence: 99%
“… 25 , 26 Psoriatic arthritis (PsA) is a seronegative spondyloarthropathy characterized by skin lesions, dactylitis, and enthesitis. 27 Patients with PsA often suffer from a number of psychosocial problems and also nonspecific symptoms early on in the course of the disease. 27 They continue to experience progressive disease due to delays in diagnosis and treatment.…”
Section: Somatization and Psoriasismentioning
confidence: 99%
“…Despite the well-established association between mental disorders and psoriasis, and the fact that early diagnosis of mental illness has proven important, mental disorders in patients with psoriasis are underrecognised and undertreated. 108 , 109 , 123 , 124 Screening for mental health disorders, especially in patients with psychiatric risk factors, and consideration of psychotherapy of patients with psoriasis are thus imperative. 105 , 111 , 117 …”
Section: Mental Disordersmentioning
confidence: 99%